Critical adsorption of periodic and random polyampholytes onto charged surfaces - Caetano, Daniel L. Z. [UNESP]; De Carvalho, Sidney J. [UNESP]; Metzler, Ralf; Cherstvy, Andrey G. (Royal Society of Chemistry (RSC), 2017)
How different are the properties of critical adsorption of polyampholytes and polyelectrolytes onto charged surfaces? How important are the details of polyampholyte charge distribution on the onset of critical adsorption transition? What are the scaling relations governing the dependence of critical surface charge density on salt concentration in the surrounding solution? Here, we employ Metropolis Monte Carlo simulations and uncover the scaling relations for critical adsorption for quenched periodic and random charge distributions along the polyampholyte chains. We also evaluate and discuss the dependence of the adsorbed layer width on solution salinity and details of the charge distribution. We contrast our findings to the known results for polyelectrolyte adsorption onto oppositely charged surfaces, in particular, their dependence on electrolyte concentration.